SOLAR DISINFECTION: A SOLUTION OF LOW COST FOR WASTE WATER TREATMENT - Queluz, J. G. T.; Alves, T. R.; Sánchez-Román, R. M. (Revista Brasileira de Engenharia de Biossistemas, 2014)
In the last decades, many studies have shown the efficiency of UV rays in the removal of pathogens from water. Solar radiation has an important component of UV radiation which affects the DNA chains of the microorganisms causing the loss of its biological activity resulting in reproduction incapacity and cell death. There are several models and ways to carry out solar disinfection. In brief, the system consists of a container which allows water exposure to solar radiation. For so, it might be used either PET or glass bottles, concrete containers, reactors, etc. These characteristics explain its low costs of installation and maintenance and, therefore, makes this technology suitable to be adopted by developing countries and/or low-income rural communities. SODIS is, therefore, a great alternative for regions with higher UV radiation incidence, where are located most part of the developing countries. Besides being an inexpensive and simple technology, SODIS does not produce toxic byproducts.